Analisa Struktur Sosial Ekonomi Masyarakat untuk Mendukung Pembangunan Desa (Studi Kasus Desa Setabu, Kecamatan Sebatik, Kabupaten Nunukan, Provinsi Kalimantan Timur) - Amongjati, Sri Anom; Sjaf, Sofyan; Mahardika, Afan Ray (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2024)
The Village Law mandates that village development be carried out independently by village, regional and national governments as well as through multi-stakeholder collaboration, so a proper analysis of the socio-economic situation in the village is needed. This research wants to present an analysis of socio-economic structure as an approach to creating appropriate village development planning, both for communities and families. Through the interview process and Focus Group Discussion (FGD) with stakeholders as well as a census of all family heads in the Village, it was found that qualitative and quantitative approaches could be used as a method for analyzing socio-economic structures based on social layers of society as a reference for development in the Village. Qualitative analysis can be used as a reference for development at the community level, while quantitative analysis can be used as a reference for development at the family and household level. These two approaches can be a reference for stakeholders in planning development so that development allocation is right on the problem and right on the subject of development in the village.